MOLECULAR TARGET AND THERAPEUTIC ASPECTS OF RHEUMATOID ARTHRITIS: A REVIEW. - Das, Biswaranjan; Samanta, Subir (Asian Journal of Pharmaceutical and Clinical Research, 2015)
Â  Rheumatoid arthritis (RA) is an autoimmune and chronic inflammatory disease. Cytokine plays a significant role in modulating the immune system and specifically the inflammation. The role of cytokines in disease has led to new development in the treatment of inflammatory diseases. Different mediator cause inflammation, and degradation of joint cartilage in RA. Some of the novel target inhibitors, which are used to treat and control this disease are cyclooxygenase-2, tumor necrosis factor-Î± (TNF-Î±), TNF-Î± converting enzyme, interleukin-1, 6, 8, 10, 12, 15, 18, matrix metalloproteinase, nuclear factor ÎºB, mitogen activated protein kinase, phosphodiesterase-4, janus kinase-signal transducer and activator of transcription, Bruton's tyrosine kinase, spleen tyrosine kinase, Phosphatidylinositol-3-kinases. The mode of action and their progress in research have been covered in this review. Keywords: Disease-modifying anti-rheumatic drugs, Tumor necrosis factor-Î± converting enzyme, Tumor necrosis factor-Î±, Janus kinase, Spleen tyrosine kinase, Phosphatidylinositol-3-kinases (PI3K).